Odpowiedzi

  • Użytkownik Zadane
2010-03-16T14:23:49+01:00
Obiętość = a *b *c
obiętość = 6*3*9=18*9=72cm3
pc=6*9*2+3*9*2+6*3*2=108+54+36=198cm²


obiętość = a *b *c
obiętość = 6*6*4,2=36*4,2=151,2cm3
p=6*6*2+6*4,2*4=72+100,8=172,8dm²

obiętość = a *b *c
obiętość = 2*0,4*0,28=0,8*0,25=0,2cm3
p=2*2*0,4+2*2*0,28+2*0,4*0,28=1,6+1,12+0,22 = 2,94m²
2 1 2
2010-03-16T14:27:18+01:00
A) a = 6cm, b = 3cm, c = 9cm.
v=6*3*9=18*9=162cm³
Ppc=6*9*2+3*9*2+6*3*2=108+54+36=198cm²

b) a = 6dm, b = 60cm, c = 4.2dm
v=6dm*6dm*4,2dm=151.2dm³
p=6*6*2+6*4,2*4=72+100,8=172,8dm²

c) a = 2m, b = 0,4m, c =2,8dm
v=2*0,4*0,28=0,22m³
p=2*2*0,4+2*2*0,28+2*0,4*0,28=1,6+1,12+0,22 = 2,94m²
1 5 1
  • Użytkownik Zadane
2010-03-16T14:30:19+01:00
V=a×b×c
Pc=2a+2b+2c

a)
V=6cm×3cm×9cm
V=162 cm³
Pc=2×6+2×3+2×9
Pc=36 cm²

b)
V=6dm×6dm×4.2dm
V=151,2 dm³
Pc=2×6+2×6+2×4,2
Pc=32,4 dm²

c)
V=2m×0,4m×0,28m
V=0,224 m³
Pc=2×2m+2×0,4m+2×0,28m
Pc=5,36 m²
1 5 1